2021
DOI: 10.3390/ijms22094420
|View full text |Cite
|
Sign up to set email alerts
|

Decoy Technology as a Promising Therapeutic Tool for Atherosclerosis

Abstract: Cardiovascular diseases (CVDs) have been classified into several types of disease, of which atherosclerosis is the most prevalent. Atherosclerosis is characterized as an inflammatory chronic disease which is caused by the formation of lesions in the arterial wall. Subsequently, lesion progression and disruption ultimately lead to heart disease and stroke. The development of atherosclerosis is the underlying cause of approximately 50% of all deaths in westernized societies. Countless studies have aimed to impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Their findings showed that these NF- κ B decoy ODNs exhibited a safe and beneficial effect on preventing restenosis after percutaneous coronary treatment since they prevented the apoptosis of ECs under hypoxia ( 121 ). To summarize, the use of EGR1 decoy ODNs as a novel therapy tool is critical for the prevention and treatment of coronary heart disease and restenosis after angioplasty ( 123 , 124 ) ( Figure 3 ).…”
Section: Egr-1 Plays a Vital Role In The Pathogenesis Of Car...mentioning
confidence: 99%
“…Their findings showed that these NF- κ B decoy ODNs exhibited a safe and beneficial effect on preventing restenosis after percutaneous coronary treatment since they prevented the apoptosis of ECs under hypoxia ( 121 ). To summarize, the use of EGR1 decoy ODNs as a novel therapy tool is critical for the prevention and treatment of coronary heart disease and restenosis after angioplasty ( 123 , 124 ) ( Figure 3 ).…”
Section: Egr-1 Plays a Vital Role In The Pathogenesis Of Car...mentioning
confidence: 99%
“…The treatment of AS was addressed in countless studies; despite the constant development of new therapeutic strategies and drugs (such as nanomedicine, decoy and anti-platelet drug-loaded targeted technologies) [ 98 , 99 , 100 ], lipid-lowering and anti-inflammatory drugs are currently used as the principal drug in the first- and second-line treatments to prevent coronary artery disease [ 101 , 102 ]. However, pericytes may suggest some new diagnoses and therapeutic strategies for AS and other vascular pathologies [ 13 ].…”
Section: As Treatments With Pericyte-mediated Effectsmentioning
confidence: 99%
“…Despite advances in developing novel therapies 4 – 10 , cardiovascular diseases, mainly atherosclerosis, are still the leading causes of death in the world, and these have been predicted to increase in the coming decades 3 . To circumvent the limitations of conventional therapies, there is an obvious need to provide multi-pronged therapeutic approaches that largely focus on the risk factors involved in these diseases 11 13 . Recently, nucleic acid-based therapies have been considerably developed and have revealed promising potential as a therapeutic platform in the treatment of a variety of diseases, some of which have been approved by the US Food and Drug Administration (FDA) 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent the limitations of conventional therapies, there is an obvious need to provide multi-pronged therapeutic approaches that largely focus on the risk factors involved in these diseases 11 13 . Recently, nucleic acid-based therapies have been considerably developed and have revealed promising potential as a therapeutic platform in the treatment of a variety of diseases, some of which have been approved by the US Food and Drug Administration (FDA) 13 , 14 . Clinical trial-based studies have demonstrated the efficacy of these therapeutics in the treatment of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation